Eksplorasi dan Implementasi Mikroba Indigenous Asal Limbah Batubara Sebagai agen Bioakumulator Terhadap Logam Berat Cd dan Pb - Elawati, Nunung Eni; Lestari, Catur Retno; Resputri, Fibra (Universitas Muhammadiyah Prof. Dr. Hamka, 2024)
Background: Heavy metals in the environment are a very important environmental pollution problem. Degrading and removing heavy metals does not degrade organic waste because heavy metals are non-biodegradable. Bioremediation is one technique that can be chosen to degrade metal waste. The purpose of this study was to obtain and identify native bacteria from coal waste that have the potential to reduce heavy metals or bioaccumulation. Method: samples were taken from coal waste, then isolated using the dilution method and incubated at 37˚C for 24 hours. Testing for heavy metal content by applying a microbial consortium suspension on coal waste with a mixture of planting media, then analyzed with an atomic absorption spectrophotometer. Results: 10 isolates with different color characteristics were obtained from microbial isolation. The analysis of heavy metal content showed a decrease in the heavy metal Pb in the L1 and L2 treatments but did not affect the heavy metal Cd. Conclusion: The microbial consortium isolated from PLTU coal waste shows a decrease in the heavy metal Pb in treatments L1 and L2.